2001
DOI: 10.1001/archinte.161.9.1183
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Pressure Level and the Risk of Myocardial Infarction, Stroke, and Total Mortality

Abstract: In this population-based study of older adults, although all measures of blood pressure were strongly and directly related to the risk of coronary and cerebrovascular events, SBP was the best single predictor of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
232
5
13

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(274 citation statements)
references
References 34 publications
12
232
5
13
Order By: Relevance
“…Ten treatable risk factors have been associated with 90% of the risk of ischemic or hemorrhagic stroke (O'Donnell et al., 2010). The risk profile for occurrence of MI is quite different than that for stroke (Yusuf et al., 2004), but hypertension is one important risk factor for stroke, MI or vascular cause of death (Carlson & Böttiger, 1985; Conroy et al., 2003; Håheim et al., 1993; Harmsen et al., 1990; Hu et al., 2005; Psaty et al., 2001; Qizilbash, Lewington, Duffy, & Peto, 1995; Seshadri et al., 2006) and antihypertensive treatment(s) reduces these risks (Hackam & Spence, 2007; Hankey, 2014; Mancia et al., 2013; Turnbull, 2003; Turnbull et al., 2005; Wachtell, Hornestam, et al., 2005; Wachtell, Lehto, et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Ten treatable risk factors have been associated with 90% of the risk of ischemic or hemorrhagic stroke (O'Donnell et al., 2010). The risk profile for occurrence of MI is quite different than that for stroke (Yusuf et al., 2004), but hypertension is one important risk factor for stroke, MI or vascular cause of death (Carlson & Böttiger, 1985; Conroy et al., 2003; Håheim et al., 1993; Harmsen et al., 1990; Hu et al., 2005; Psaty et al., 2001; Qizilbash, Lewington, Duffy, & Peto, 1995; Seshadri et al., 2006) and antihypertensive treatment(s) reduces these risks (Hackam & Spence, 2007; Hankey, 2014; Mancia et al., 2013; Turnbull, 2003; Turnbull et al., 2005; Wachtell, Hornestam, et al., 2005; Wachtell, Lehto, et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…8,9 In the elderly, some disagreement has surrounded the importance of monitoring and treating SBP, DBP, or both, as well as whether to treat isolated and/or borderline isolated systolic hypertension. 7,[10][11][12][13] Further, in the very elderly, older than 80 years, BP elevations have shown an association with better survival. [14][15][16] Despite these areas of controversy, treatment is commonly recommended for identified hypertension in the elderly and in middle-aged adults, as participants with stage 1 or 2 hypertension have shown that lowering systolic pressure by 10-12 mm Hg and diastolic pressure by 5-6 mm Hg reduces CVD event rates.…”
Section: Introductionmentioning
confidence: 96%
“…21 In the women of Finnmark Study, DBP was associated with incident diabetes in the age-adjusted model but not in the multivariable-adjusted model. 22 Although many studies examined PP and MAP as predictors of CVD, 23,24 there is lack of data regarding the effect of these components for prediction of diabetes, compared with other BP components. Kramer et al 21 in the Rancho Bernardo study showed that 10 mm Hg increases in PP causes a 20% increase in risk of diabetes in the multivariable-adjusted model.…”
Section: Discussionmentioning
confidence: 99%